(untitled) (Fiep Bulletin - online, 2012)
Aerobic physical activity is one of the main pillars of non-pharmacological treatment in hypertensive patients. There is evidence that regular practice of aerobic exercises, such as 30 or 40 minute brisk walk, 3 or 4 times a week can lower blood pressure. With isotonic physical activity, progressive and systematic than 20 minutes a day, there has been a decrease in mortality from cardiovascular causes by 30%. By contrast, sedentary normotensive individuals have a 20% and 50% increased risk of developing hypertension when compared with those who keep trained.The benefit of exercise can not be attributed solely to lower blood pressure, since the practice of it favorably modifies blood lipids, heart rate decreases reflecting a lower sympathetic nerve activity increases vasodilator prostaglandins, renin activity decreases plasma and improves insulin sensitivity.Awareness of body care practitioners making physical exercises comply with proper diet, low alcohol and fat. In addition, the feeling of being attributed to increased exercise-induced endorphins, brings a better quality of life.For all of the prefix, there seems no reason to limit the practice of aerobic physical activity in patients with mild to moderate hypertension. Only those with cardiovascular disease or other serious health problems need further evaluation before a workout, which in some cases should be medically supervised.